2022
DOI: 10.1111/spc3.12707
|View full text |Cite
|
Sign up to set email alerts
|

The promises and pitfalls of functional magnetic resonance imaging hyperscanning for social interaction research

Abstract: Social neuroscience combines tools and perspectives from social psychology and neuroscience to understand how people interact with their social world. Here we discuss a relatively new method-hyperscanning-to study real-time, interactive social interactions using functional magnetic resonance imaging (fMRI). We highlight three contributions that fMRI hyperscanning makes to the study of the social mind: (1) Naturalism: it shifts the focus from tightly-controlled stimuli to more naturalistic social interactions; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 145 publications
0
4
0
1
Order By: Relevance
“…In recent years, however, a growing number of studies have shown that alignment – also often referred to as synchrony – can be socially meaningful in a variety of modalities, including movement, language, neurophysiology, and pupil dilation ( Pan et al, 2022 ; Nguyen et al, 2021 ); Wohltjen and Wheatley, 2021 ; Pickering and Garrod, 2021 ; Dikker et al, 2021b ). Here, we focus on neural synchrony, or inter-brain coupling, which has been associated with a range of communicative outcomes, including language comprehension, socio-emotional connectedness, learning, and even pain perception ( Goldstein et al, 2018 , Dumas et al, 2010 , Wass et al, 2020 , Davidesco et al, 2023 ; for reviews see e.g., Czeszumski et al, 2022 , Czeszumski et al, 2020 ; Koike et al, 2015 ; Tsoi et al, 2022 ; Babiloni and Astolfi, 2014 ; Toppi et al, 2016 ; Liu et al, 2018 ; Nguyen et al, 2020 ; Reindl et al, 2018 ; Marriott Haresign et al, 2022 ).…”
Section: Neural Alignment In Children Adults and Grandparentsmentioning
confidence: 99%
“…In recent years, however, a growing number of studies have shown that alignment – also often referred to as synchrony – can be socially meaningful in a variety of modalities, including movement, language, neurophysiology, and pupil dilation ( Pan et al, 2022 ; Nguyen et al, 2021 ); Wohltjen and Wheatley, 2021 ; Pickering and Garrod, 2021 ; Dikker et al, 2021b ). Here, we focus on neural synchrony, or inter-brain coupling, which has been associated with a range of communicative outcomes, including language comprehension, socio-emotional connectedness, learning, and even pain perception ( Goldstein et al, 2018 , Dumas et al, 2010 , Wass et al, 2020 , Davidesco et al, 2023 ; for reviews see e.g., Czeszumski et al, 2022 , Czeszumski et al, 2020 ; Koike et al, 2015 ; Tsoi et al, 2022 ; Babiloni and Astolfi, 2014 ; Toppi et al, 2016 ; Liu et al, 2018 ; Nguyen et al, 2020 ; Reindl et al, 2018 ; Marriott Haresign et al, 2022 ).…”
Section: Neural Alignment In Children Adults and Grandparentsmentioning
confidence: 99%
“…Additionally, in these reviewed EEG and fMRI studies, researchers forecasted market‐level outcomes by calculating correlations between different individuals' brain responses to the same stimulus. This approach, also known as inter‐subject correlation (ISC) or neural synchrony, is commonly utilized in hyperscanning studies (Babiloni & Astolfi, 2014; Tsoi et al, 2022). In this section, we will briefly describe the origins of this concept and the underlying mechanisms it reflects.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While fNIRS is a more popular hyperscanning approach than fMRI, fMRI has clear superiority in the degree of spatial resolution and whole brain coverage (including cerebellum and subcortex) that can be achieved [70,71]. Nevertheless, the high cost and low mobility of fMRIhyperscanning units mean that pseudo-hyperscanning (asynchronous interactions using recorded stimuli and sequential but not synchronized scanning) has been the more commonly employed approach with fMRI [75,[94][95][96].…”
Section: Fnirs and Fmri Hyperscanningmentioning
confidence: 99%